High spin-wave propagation length consistent with low damping in a metallic ferromagnet - Flacke, Luis (Appl Phys Lett, 2019)
We report ultralow intrinsic magnetic damping in Co(25)Fe(75) heterostructures, reaching the low 10(−4) regime at room temperature. By using a broadband ferromagnetic resonance technique in out-of-plane geometry, we extracted the dynamic magnetic properties of several Co(25)Fe(75-)based heterostructures with varying ferromagnetic layer thicknesses. By measuring radiative damping and spin pumping effects, we found the intrinsic damping of a 26 nm thick sample to be α(0) ≲ 3.18 × 10(−4). Furthermore, using Brillouin light scattering microscopy, we measured spin-wave propagation lengths of up to (21 ± 1) μm in a 26 nm thick Co(25)Fe(75) heterostructure at room temperature, which is in excellent agreement with the measured damping.